Modern Diagnostics and Treatment in the Field of Pediatrics - Umarova Mukaddaskhon Abdukadirovna (Zien Journals, 2023)
In this article, feedback on diagnostics and treatment will be discussed in the field of Pediatrics. Pediatrics has undergone many changes in recent years due to advancements in technology, research, and healthcare practices. There is an increasing focus on preventive care in Pediatrics, which involves regular check-ups, screening tests, and vaccinations to prevent disease and promote overall health and wellness. Technology in Diagnosis and Treatment as mentioned earlier, the use of technology in diagnosing and treating pediatric illnesses has been a significant change. There are digital medical records, telemedicine, and many diagnostic tools, such as genetic testing, imaging, and biomarker testing
Keywords: Pediatrics; diagnostics; treatment; modern examinations